Preoperative and perioperative intervention reduces the risk of recurrence of endometriosis in mice caused by either incomplete excision or spillage and dissemination. Issue 3 (September 2021) - Chen, Yishan; Liu, Xishi; Guo, Sun-Wei
Abstract: Research question: Can preoperative or perioperative intervention reduce the risk of recurrence of endometriosis caused by either incomplete excision or spillage and dissemination? Design: A mouse model of endometriosis recurrence caused by spillage and dissemination was first established using 24 female Balb/c mice. The spillage and dissemination model was used to test the efficacy of preoperative use of ketorolac, perioperative use of aprepitant and combined use of propranolol and andrographolide in a prospective, randomized mouse experiment involving 75 mice. The efficacy of these preoperative and perioperative interventions in a mouse recurrence model caused by incomplete excision was also tested using 72 mice. In all experiments, the baseline body weight and hotplate latency of all mice were measured and recorded before the induction of endometriosis, before the primary surgery and before sacrifice. In addition, all lesions were excised, weighed and processed for quantification and immunohistochemistry analysis of E-cadherin, α-SMA, VEGF, ADRB2 and putative markers of recurrence PR-B, p-p65, as well as Masson trichrome staining. Results: All interventions substantially and significantly suppressed the outgrowth of endometriotic lesions and reduced the risk of recurrence caused by either spillage and dissemination or incomplete excision ( P = 0.0007 to 0.042). These interventions also significantly attenuated the generalized hyperalgesia, inhibited the staining of α-SMA, p-p65, VEGF and ADRB2 but increased staining of E-cadherin and PR-B, resulting in reduced fibrosis. Conclusion: Given the excellent safety profiles of these drugs, these data strongly suggest that preoperative and perioperative intervention may potentially reduce the risk of endometriosis recurrence effectively.